Upaya Meningkatkan Keterampilan Berbicara Siswa Melalui Metode Storytelling Untuk Siswa Kelas Rendah - May Indah sari; Fitri Maisyurah (Institut Nalanda, 2024)
This research is Classroom Action Research regarding the application of the storytelling method. The aim of this research is to determine the effect of the storytelling method and taking a communicative approach in improving the speaking skills of second grade elementary school students. The background to this research is that the speaking skills of second grade elementary school students are still low. This research was carried out in two cycles consisting of planning, implementation, observation and reflection stages. The subjects in this research were 23 grade II elementary school students in Langkat Regency. The learning steps using the storytelling method consist of three stages, namely the stage of opening or starting the activity, the stage of telling the story, and the stage of closing the story and evaluating. The results of the research show that each cycle experiences an increase. This can be seen from the assessment of students' speaking skills in cycle I, which was 71 and cycle II, which was 80.4. The completion rate in cycle I was 60.9% and in cycle II was 87%. From the implementation of cycle I and cycle II, students' speaking skills increased by 26.1%. Based on the research results above, it can be concluded that the storytelling method with a communicative approach can improve students' speaking skills.